An overview of As(V) removal from water by adsorption technology - Renda Yao; Hong Yang (Annals of Musculoskeletal Medicine - Peertechz Publications, 2020)
Adsorption has been widely used for arsenic-contaminated drinking water treatment. The mechanism of As(V) removal from water by adsorption technology was brief introduced, and the influence factors of different adsorption pathways were also illustrated. The materials used as adsorbents were classified according to physical, chemical and biological processes, and the effect on As(V) removal from water using a variety of adsorbents were overviewed in this study. The current problems of this technology were also discussed, then, the solutions and development directions were put forward. Adsorption capability provides significant reference when selecting an adsorbent. Therefore, to develop environmental friendly materials achieving efficient adsorption capabilities, optimize the synthesis and modification methods of the current adsorbents, and improve regeneration efficiency are the trends of developing adsorption technique on As(V) removal from water. Biological arsenic removal technology has the advantages due to good effect, low cost and less secondary pollution, which have bright development and application prospects. Local conditions of arsenic-contaminated water, practical feasibility of the adsorption technology and applicable conditions of each material should be comprehensively compared and evaluated, when selecting specific adsorbent for As(V) removal from water.